Synthesis of acrylic resin and methacrylic resin microspheres by suspension polymerization - Yu, Han; Liu, Junjie; Zhao, Lin; Liu, Yonglin; Gu, Lulu; Feng, Lianxiang; Weng, Yonggen; Duan, Qingxu; Duan, Baorong; Qu, Jiale (Frontiers in Chemistry, 2023)
The process of suspension polymerization was utilized to create acrylate resin microspheres with mesh numbers of 140–200 μm and particle sizes of 100 μm for implementation in mesh coating technology. The copolymer of methyl methacrylate (MMA) and methyl acrylate (MA) served as the primary polymer, with dibenzoyl peroxide (DBPO) functioning as the initiator, and a mixture of calcium carbonate and deionized water served as the dispersion medium. The surface morphology of the synthesized microspheres was analyzed through Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) to confirm successful synthesis. The optimal reaction conditions for the synthesis of these microspheres were determined to be a dispersant dosage of 30 g of calcium carbonate with a monomer ratio of 4:1, a reaction time of 1 h, an initiator dosage of 1.2 g of BPO, and a reaction temperature of approximately 75–80 C, resulting in microspheres with a regular spherical shape and smooth surface.